Quality of service in ad hoc networks - Gwee, Choon Lim (2009)
With the onset of multimedia applications, Quality of Service (QoS) in 802.11-based wireless ad hoc networks has been an essential area to look into. Standard wireless protocols such as IEEE 802.11b and IEEE 802.11e have been deemed unsuitable for multimedia traffic transmission in an ad hoc (multihop) network environment due to the unique network characteristics. As an ad hoc network is infrastructureless and distributed in nature, it gives rise to several challenges in QoS provisioning. In this thesis, we focus on the research of three key areas on QoS in ad hoc networks namely, buffer management in the medium access control (MAC) layer, cross-layer design and flow admission control. Firstly, we study MAC layer buffer management in the IEEE 802.11e protocol. The IEEE 802.11e MAC protocol provides QoS for multimedia traffic by probabilistic priority queueing. Ad hoc networks tend to generate a large volume of network control packets for route maintenance and these control packets are typically queued in the highest priority queue. As a result, higher priority control traffic is always being served, consuming most of the bandwidth and results in poor network performance for data traffic. We examine this problem and propose a dynamic buffer management scheme to mitigate it. By setting different threshold levels in different priority queues, we allow lower priority data traffic to be served when the higher priority control traffic is deemed to be excessive. Simulation of our proposed scheme has shown that our approach yielded better network performance compared to the standard protocol in terms of packet delivery ratio and average delay. Secondly, we study the cross-layer interaction between the MAC and Network layers to identify its impact on QoS. We select the IEEE 802.11e MAC protocol and Ad-hoc On Demand Distance Vector (AODV) routing protocol in our study since they are standardized protocols for wireless networks. In IEEE 802.11e MAC protocol, lower priority traffic has a higher probability of being blocked. Hence, the MAC layer will inform the Network layer of a broken link through the link notification function. In this case, AODV will re-route the paths that traverse this link. As a result, higher priority traffic which shares the same link as the lower priority traffic will undergo the same re-routing procedures. We termed this phenomenon path correlation effect. Under high traffic load, the path correlation effect will be more intense and hence degrade the QoS of higher priority traffic. To break the path correlation effect, we propose a cross-layer design called the Bundled Virtual Circuit (BVC). Our proposed BVC scheme not only addresses the path correlation issues, but also provides priority treatment from the Network layer to the MAC layer. Through our simulations, our proposed cross-layer design approach is proven to provide better network performance than the 802.11e/AODV protocols in terms of packet delivery ratio and delay. Finally, we examine flow admission control at the routing layer in ad hoc networks. Standard routing protocols such as AODV performs routing on a shortest path basis. In the presence of multiple routes, hotspots are likely to form among the intermediate nodes and thus lead to network congestion. In addition, existing routes are not well-protected from the introduction of new routes. We propose a flow admission control algorithm to be used with AODV. Our algorithm allows routes to be created through available bandwidth and congestion estimation. During the route discovery phase, each node will be gauged on its estimated available bandwidth and its backlog of packets in the MAC buffer. If a node does not have sufficient bandwidth, or has too many backlogged packets compared to the requested flow rate, it will not participate in the route discovery process. From simulations, our new scheme is able to provide better network performance than the standard AODV protocol in terms of delay. Our work in this thesis focuses on QoS provisioning in ad hoc networks from the MAC and network layer perspectives. By studying the network characteristics and protocols’ behavior, we investigate the various problems of providing QoS in an ad hoc network environment and propose three different schemes to improve the QoS provisioning at the MAC and network layers. We believe that our work is able to provide some insights to the research area on QoS in ad hoc networks.